Nalar Kritis Atas Positivisme Hukum Studi terhadap Perda Syariat di Indonesia - Agus Purnomo (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
This paper seeks to find the rationale for the preparation of the Sharia Regional Regulation by referring to the epistemology of its preparation. The research begins by re-examining the existing epistemology in legal science, namely between legal positivism and legal realism. Each school of thought will be formulated with its characteristicsThe characteristics of each school of thought will be formulated and then matched with the characteristics that exist in the preparation of Sharia local regulations and analyzed. Based on the characteristics identified, it is found that the preparation of Sharia local regulations follows the positivistic paradigm. This is based on several similarities, namely: a) Sharia local regulations lacka) Sharia local regulations do not consider the socio-juridical implications, b) Sharia local regulations “force” to legislate abstract and private Sharia values, c) Legislation is urgent, d) Sharia local regulations are more concerned with the positivization process than formulating the substance. From some of the characteristics as stated above, the implication is that Sharia local regulations receive criticism as the positivistic paradigm of thought, namely: a) The ambiguity of the formalization of the Sharia Regional Regulation: Between Law and Morals, b) Ineffective Legislation of Local Regulations, c) Violating Human Rights, d) Having a Motive ofHuman Rights, d) Having Political Motives and e) Sharia Regional Regulation is only Symbolic.